The Effect of High Targets in The Development of Infrastructure and Organizational Culture on Organizational Commitments to Employees and Performance - Budiwibowo, Triyono; Komariyah, Erna Fitri (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2023)
This study provides evidence that achieving performance at high targets in infrastructure development requires an OCE and organizational culture. This study is driven by the high target for infrastructure development in Indonesia from 2015 to 2020 as a strategic policy to help support economic growth and fair distribution of social welfare. Multigroup Analysis assesses the moderating effects of the high target in infrastructure development and organizational culture. This result suggests that OCE has a positive impact on motivation, which subsequently has a significant impact on performance. Moreover, motivation has been shown to moderate the relationship between high targets and OCE. On the other hand, this finding shows that achieving high infrastructure development targets requires a strong organizational culture that will impact performance positively and significantly through increased motivation.